Let's complete the process of solving the equation step by step, filling in the missing terms and descriptions as needed.
-
Starting with the original equation: \[ -15(-6t + 6) + 15 = 18t - 3 \]
-
Apply the distributive property: \[ -15(-6t) + (-15)(6) + 15 = 18t - 3 \] This simplifies to: \[ 90t - 90 + 15 = 18t - 3 \]
-
Combine like terms on the left side: \[ 90t - 75 = 18t - 3 \]
-
Subtract \(18t\) from both sides: \[ 90t - 18t - 75 = -3 \] This simplifies to: \[ 72t - 75 = -3 \]
-
Add \(75\) to both sides: \[ 72t = -3 + 75 \] Thus: \[ 72t = 72 \]
-
Divide both sides by \(72\): \[ t = \frac{72}{72} \] Therefore: \[ t = 1 \]
Summary of Steps:
- Original Equation: \( -15(-6t + 6) + 15 = 18t - 3 \)
- Apply the distributive property.
- Combine like terms: \( 90t - 75 = 18t - 3 \)
- Subtract \( 18t \) from both sides.
- Add \( 75 \) to both sides.
- Divide by \( 72 \): \( t = 1 \)
Missed Terms and Descriptions:
- Apply the distributive property
- Combine like terms
- Subtract \( 18t \) from both sides
- Add \( 75 \) to both sides
- Divide both sides by \( 72 \)
Final solution: \[ t = 1 \]